Boron removal from metallurgical grade silicon and Si-Sn alloy through slag refining with gas blowing - Rowaid Al-khazraji; Yaqiong Li; Lifeng Zhang (Functional Materials, 2018)
A combined method of slag refining and gas blowing technique were used for boron removal from metallurgical grade silicon and 75%wt Si-Sn alloy using the 45%CaO-45%SiO₂-10%CaCl₂ slag with the use of Ar gas and Ar-20%O₂ mixed gas. Increasing gas flow rate from 50 to 250 ml/min shows enhancement in B removal. At fixed conditions the Ar-20%O₂ mixed gas blowing shows a good removal efficiency of boron about 85% and 96% to MG and Si-Sn alloy respectively, compared with the single Ar gas blowing with 78.6% and 88% to MG and Si-Sn alloy respectively. Changes in slag composition representing by decreasing in all compounds especially CaCl₂ attached with increase in Al₂O₃. The B impurities after the treatment found with low intensity in Si matrix but with high intensity in slag phase and Sn phase. Boron removal controlled by mass transfer in slag phase with mass transfer coefficients of 3.38ċ10⁻⁴cm.s⁻¹ and 7.2ċ10⁻⁵cm.s⁻¹ in Si and Si-Sn alloy respectively.